Recent Advancement in Drug Development for Treating Malaria using Herbal Medicine and Nanotechnological Approach - Bhargava, Sarvesh; Deshmukh, Rohitas; Dewangan, Hitesh Kumar (Current Pharmaceutical Design, 2025)
More than two hundred million people around the world are infected with malaria, a blood-borne disease that poses a significant risk to human life. Single medications, such as lumefantrine, primaquine, and chloroquine, as well as combinations of these medications with artemisinin or its derivatives, are currently being used as therapies. In addition, due to rising antimalarial drug resistance, other therapeutic options are needed immediately. Furthermore, due to anti-malarial medication failures, a new drug is required. Medication discovery and development are costly and time-consuming. Many malaria treatments have been developed however, most treatments have low water solubility and bioavailability. They may also cause drug-resistant parasites, which would increase malaria cases and fatalities. Nanotechnology may offer a safer, more effective malaria therapy and control option. Nanoparticles' high loading capacity, concentrated drug delivery, biocompatibility, and low toxicity make them an attractive alternative to traditional therapy. Nanotechnology-based anti-malarial chemotherapeutic medications outperform conventional therapies in therapeutic benefits, safety, and cost. This improves patient treatment compliance. The limitations of malaria treatments and the importance of nanotechnological approaches to the treatment of malaria were also topics that were covered in this review. The most recent advancements in nanomaterials and the advantages they offer in terms of medication delivery are discussed in this article. The prospective therapy for malaria is also discussed. Additionally, the limitations of malaria therapies and the importance of nanotechnology-based approaches to the treatment of malaria were explored.
Keywords: drug delivery